2006
DOI: 10.1086/508607
|View full text |Cite
|
Sign up to set email alerts
|

Mid?Infrared Observations of T Tauri Stars: Probing the Star?Disk Connection in Rotational Evolution

Abstract: We present mid-IR N-band (λ ef f = 10.2µm) photometry of a carefully selected sample of T Tauri stars thought to be single from the Taurus-Auriga molecular cloud. Infrared excesses in these stars are generally attributed to circumstellar dust-disks. Combining observations at 2.16µm (K s -band) and 10.2µm (N-band) we probe a region in the circumstellar dust-disk from a few stellar radii through the terrestrial planet zone (0.02-1.0AU). By analyzing the distribution of the (K s − N) color index with respect to p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…This indicates that a very efficient mechanism is at work to remove the angular momentum in these stars; the nature of this mechanism is still controversial. Kundurthy et al (2006), see also Edwards et al (1993), claimed that CTTS are slow rotators with circumstellar disks, while WTTS are fast rotators without accretion disks. However, the association of CTTS with slow rotators and WTTS with fast ones is not as yet observationally confirmed.…”
Section: The Angular Momentum Problem Observational Factsmentioning
confidence: 98%
“…This indicates that a very efficient mechanism is at work to remove the angular momentum in these stars; the nature of this mechanism is still controversial. Kundurthy et al (2006), see also Edwards et al (1993), claimed that CTTS are slow rotators with circumstellar disks, while WTTS are fast rotators without accretion disks. However, the association of CTTS with slow rotators and WTTS with fast ones is not as yet observationally confirmed.…”
Section: The Angular Momentum Problem Observational Factsmentioning
confidence: 98%
“…(Continued) where N is the number of measurements, μ i are the reported magnitudes, and σ At longer infrared wavelengths, the SEDs shown in Figure 13(a) were collected primarily from Spitzer imaging surveys (Luhman et al 2010;Rebull et al 2010), the Wide-field Infrared Survey Explorer all-sky catalog (Wright et al 2010), the AKARI point source catalogs (Ishihara et al 2010), and the Infrared Astronomical Satellite (IRAS) point source catalog (Beichman et al 1988), with some additional ground-and space-based measurements (Strom et al 1989;Hillenbrand et al 1992;Malfait et al 1998 Metchev et al 2004;Pantin et al 2005;McCabe et al 2006McCabe et al , 2011Kundurthy et al 2006;Mariñas et al 2006;Bouy et al 2008;Monnier et al 2008;Ratzka et al 2009;Duchêne et al 2010;Honda et al 2010;Skemer et al 2010;Wahhaj et al 2010;Gräfe et al 2011;Harvey et al 2012). In addition to the new data presented here (see Table 1), integrated flux density measurements in the submillimeter-radio spectrum are compiled from various catalogs in the literature (Weintraub et al 1989;Adams et al 1990;Beckwith et al 1990;Beckwith & Sargent 1991;Altenhoff et al 1994;Jewitt 1994;Mannings & Emerson 1994;Jensen et al 1994;Koerner et al 1995;Osterloh & Beckwith 1995;…”
Section: Appendix a Spectral Energy Distributionsmentioning
confidence: 99%
“…It has been suggested that during the pre-main-sequence phase of evolution, rotation is likely regulated by magnetic coupling to a circumstellar disk (e.g., Edwards et al 1993;Kundurthy et al 2006), although this mechanism is still a matter of debate (e.g., Stassun et al 1999;Nguyen et al 2009). Once the disk dissipates in ∼1-10 Myr , a star or VLM object will speed up due to its continued contraction.…”
Section: Intrinsic Rotational Velocity Differences?mentioning
confidence: 99%